Pharyngeal pH monitoring in gastrectomy patients – what do we really measure?. Issue 4 (August 2016) - Wilhelm, Dirk; Jell, Alissa; Feussner, Hubertus; Schmid, Roland M; Bajbouj, Monther; Becker, Valentin
Aim: Diagnosis of laryngopharyngeal reflux (LPR) has dramatically increased over the last years. For diagnosis of gastroesophageal reflux, a newly designed pharyngeal probe (Dx-pH) was recently introduced. It is also recommended to guide therapy decision in antireflux surgery. However, diagnostic results are questionable. Therefore, we establish a reliable reference group with asymptomatic patients after total gastrectomy and, thus, complete extinction of gastric acid production. Methods: Pharyngeal pH monitoring was performed in 10 consecutive patients with history of total gastrectomy. All patients were off proton pump inhibitor (PPI) therapy and followed a non-acid diet during the complete measurement period. Results: All procedures were performed without any complication. Six of the 10 asymptomatic gastrectomy patients (60%) had pathological results derived from the validated reference values (Ryan score) in pharyngeal pH monitoring. Conclusion: Pathological pH values assessed by the Dx-pH device, usually interpreted as pathological aerosolized acidic gastroesophageal and/or laryngopharyngeal reflux, are obviously dissociated from gastric acid production. Further studies are required to determine diagnostic value of the new system. Therefore, the pharyngeal pH monitoring system seems currently not to be useful to guide any diagnostic or therapeutic decisions, in particular if surgical therapy is considered.